2018
DOI: 10.1016/j.neuroimage.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the orientation of contrast edges from MEG evoked and induced responses

Abstract: Visual gamma oscillations have been proposed to subserve perceptual binding, but their strong modulation by diverse stimulus features confounds interpretations of their precise functional role. Overcoming this challenge necessitates a comprehensive account of the relationship between gamma responses and stimulus features. Here we used multivariate pattern analyses on human MEG data to characterize the relationships between gamma responses and one basic stimulus feature, the orientation of contrast edges. Our f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 70 publications
(118 reference statements)
1
45
0
Order By: Relevance
“…A useful tool for comparing data from different modalities has been representational similarity analysis 18,37,39,40,[44][45][46][47][48][49] . This technique can quantitatively relate brain-activity measurements, such as fMRI, with computational models, such as DCNNs, by abstracting the data into representational space using matrices of pairwise similarity (a representational dissimilarity matrix-RDM).…”
Section: Resultsmentioning
confidence: 99%
“…A useful tool for comparing data from different modalities has been representational similarity analysis 18,37,39,40,[44][45][46][47][48][49] . This technique can quantitatively relate brain-activity measurements, such as fMRI, with computational models, such as DCNNs, by abstracting the data into representational space using matrices of pairwise similarity (a representational dissimilarity matrix-RDM).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to assess whether the two experimental conditions were differentiated by neural patterns stable over time, we performed a temporal generalization multivariate analysis. The algorithm was the same as the one described above, with the difference that in this case we used each time-point of the training set to predict not only the same time-point in the testing set, but all time-points [58,59,60].…”
Section: Multivariate Pattern Analysismentioning
confidence: 99%
“…We tested our hypothesis based on predictive coding following the proposal of Lewis and Bastiaansen (). Previous studies have shown that synchronization between cortical areas may indicate communication between those areas, with the phase locking values as a measure of synchrony (Doesburg, Kitajo, & Ward, ; Fries, , ; Panagiotaropoulos, Deco, Kapoor, & Logothetis, ; Pantazis et al, ; Tallon‐Baudry & Bertrand, ; Weeks et al, ). Phase locking values were estimated between cortical areas involved in semantic processing.…”
Section: Introductionmentioning
confidence: 99%